The Earth Hologenome Initiative : Data Release 1 - Gaun, Nanna; Pietroni, Carlotta; Martin-Bideguren, Garazi; Lauritsen, Jonas; Aizpurua, Ostaizka; Fernandes, Joana M.; Ferreira, Eduardo; Aubret, Fabien; Sarraude, Tom; Perry, Constant; Wauters, Lucas; Romeo, Claudia; et al. (GigaScience, 2025)
Background: The Earth Hologenome Initiative (EHI) is a global endeavor dedicated to revisit fundamental ecological and evolutionary questions from the systemic host–microbiota perspective, through the standardized generation and analysis of joint animal genomic and associated microbial metagenomic data. Results: The first data release of the EHI contains 968 shotgun DNA sequencing read files containing 5.2 TB of raw genomic and metagenomic data derived from 21 vertebrate species sampled across 12 countries, as well as 17,666 metagenome-assembled genomes reconstructed from these data. Conclusions: The dataset can be used to address fundamental questions about host–microbiota interactions and will be available to the research community under the EHI data usage conditions.
Keywords: Bacteria; Genome; Genome-resolved metagenomics; MAG; Metagenome-assembled genome; Metagenomics; Microbiome; Microbiota